Investigation on microwave heating for direct leaching of chalcopyrite ores and concentrates - Onol, Kubra; Saridede, Muhlis Nezihi (SPRINGER, 2013)
The use of microwave energy in materials processing is a relatively new development presenting numerous advantages because of the rapid heating feature. Microwave technology has great potential to improve the extraction efficiency of metals in terms of both a reduction in required leaching time and an increase in the recovery of valuable metals. This method is especially pertinent in view of the increased demand for environment-friendly processes. In the present study, the influence of microwave heating on the direct leaching of chalcopyrite ores and concentrates were investigated. The results of microwave leaching experiments were compared with those obtained under conventional conditions. During these processes, parameters such as leaching media, temperature, and time have been worked to determine the optimum conditions for proper copper dissolution. Experimental results show that microwave leaching is more efficient than conventional leaching. The optimum leaching conditions for microwave leaching are the solid-to-liquid ratio of 1: 100 g/mL, the temperature of 140 degrees C, the solution of 0.5 M H2SO4 + 0.05 M Fe-2(SO4)(3), and the time of 1 h.
Keywords: hydrometallurgy; chalcopyrite; leaching; microwave heating; Materials Science; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing